2013
DOI: 10.1186/1756-0500-6-278
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women’s knowledge of weight, weight gain, complications of obesity and weight management strategies in pregnancy

Abstract: BackgroundObesity is increasingly common in the obstetric population. Maternal obesity and excess gestational weight gain (GWG) are associated with increased perinatal risk. There is limited published data demonstrating the level of pregnant women’s knowledge regarding these problems, their consequences and management strategies.We aimed to assess the level of knowledge of pregnant women regarding: (i) their own weight and body mass index (BMI) category, (ii) awareness of guidelines for GWG, (iii) concordance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
76
2
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 32 publications
10
76
2
13
Order By: Relevance
“…Consistent with Shub et al [22], over a third of the women in this study had no knowledge of the GWG guidelines. Some women reported being “completely unaware” or “not being able to remember” the guidelines whereas others said they did not receive GWG information from their physician.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Consistent with Shub et al [22], over a third of the women in this study had no knowledge of the GWG guidelines. Some women reported being “completely unaware” or “not being able to remember” the guidelines whereas others said they did not receive GWG information from their physician.…”
Section: Discussionsupporting
confidence: 79%
“…One study by de Jersey, Nicholson, Callaway, and Daniels [21] did examine knowledge of dietary recommendations and found that participants knew limited information about the correct recommended daily number of servings of fruit (8%) and vegetables (36%); only 4% of participants actually consumed the recommended five servings/day of vegetables. Another study by Shub, Huning, Campbell, and McCarthy [22] found that 64% of obese women and 40% of overweight women overestimated their GWG and had poor knowledge of the risks associated with high GWG and maternal obesity.However, research examining pregnant women's knowledge of healthy eating behaviors as they relate to GWG is scant. This research is needed to develop effective interventions promoting healthy eatingbehaviors in an effort to better manage GWG.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 This difference may relate to the nature of the survey items. The New Beginnings study asked participants to report the likelihood of each condition occurring, worded as it applies to the respondent, whereas the comparative studies 15,16,27 assessed knowledge as it applied to any pregnant woman. It is possible to acknowledge a health risk without accepting personal susceptibility to the threat.…”
Section: Discussionmentioning
confidence: 99%
“…Pri tome su neočekivano visokoobrazovane trudnice potcenile tu optimalnu vrednost, što nam ukazuje da edukativne mere treba usmeriti na sve trudnice nezavisno od pariteta i stepena obrazovanja. Naši rezultati su u skladu sa rezultatima Shuba i saradnika [8], kao i Downsa i saradnika, koji navode da 42% žena ne zna koja je preporučena masa koju treba dodati tokom trudnoće [9].…”
Section: Materijal I Metodunclassified